Enhancing Braille education: usability, perception, and design considerations of a Graphical User Interface - Esam, Asrizam; Nordin, Mohd Norazmi; Hashim, Siti Noor Aneeis; Mohd Idris, Nor Diana; Maidin, Siti Sarah; Krishnan, Vijayaletchumy; Abbas, Mohd Saleh (UK Zhende Publishing Press, 2024)
The study examined the usability, perception, and design considerations of a Graphical User Interface (GUI) aimed at enhancing Braille education. A total of 110 participants, with a mean age of 28.4 years, participated, with a balanced gender distribution and varying education levels. Results from participant perceptions revealed high ratings for the GUI's usability, with mean scores ranging from 4.6 to 4.8 out of 5. Comparisons between blind individuals and educators indicated overall positive perceptions of the GUI, with blind individuals showing slightly higher ratings. Participant feedback highlighted key design features such as clear layout, interactive elements, customizable settings, and real-time feedback. In-depth interviews identified themes emphasizing accessibility and inclusivity, personalized learning experiences, collaboration, feedback mechanisms, and integration with existing curriculum as crucial for effective Braille education using the GUI.